IMPLEMENTASI KEBIJAKAN PENEMPATAN TENAGA KERJA INDONESIA DI LUAR NEGERI DI KABUPATEN PATI - Jannah, Nikmatul Nur; Suryaningsih, Margaretha (Journal of Public Policy and Management Review, 2018)
Implementation of overseas migrant placement policy is one of the efforts undertaken by the Government of Pati Regency to overcome the problems associated with placement of migrant workers from Pati Regency who work abroad. The method used in this research is qualitative method of descriptive type. The purpose of this study is to see how the implementation of Indonesian employment policy abroad in Pati Regency as well as describe the factors that are considered to influence the implementation of policies according to Van Meter and Van Horn theory. The result of the research shows that in the implementation of the policy, there are problems related to registration, reporting, and data service and information of TKI. Factors considered to be inhibiting the implementation of the policy of placement and protection of Indonesian workers abroad in Pati Regency concerning the policy objectives, resources, and social conditions of TKI in Pati Regency.